1996
DOI: 10.1097/00000478-199611000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing Cellular Dermatofibroma

Abstract: Two cases of metastasizing cellular dermatofibroma (cutaneous fibrous histiocytoma) are presented. The first patient, an 18-year-old man, had a nodule excised from his right upper thigh. He developed three local recurrences at 1.5, 2, and 2.5 years and metastasis to inguinal lymph nodes. He underwent lung segmentectomies for metastases 1.5 and 4 years later and was alive with no evidence of tumor at latest follow-up, which was 15 months after the last surgery. The second patient, a 33-year-old man, had a nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 5 publications
1
38
0
2
Order By: Relevance
“…In most cases, there is a long delay (range, 4 to 228 months; median, 40 months) between the excision of the primary skin lesion and the emergence of metastases. Actually, long-term follow-up shows that those metastases, whatever their location, are characteristically slow-growing lesions, which justifies the iterative metastasectomy approach in case of pulmonary involvement (7,8). This is exemplified by Patient 1 of our series in whom a progressive inguinal lymph node enlargement was noticed as long as 13 years before inguinal lymphadenectomy and also by Patient 2 of Colome-Grimmer and Evans's report (7), who survived 8 years after his lung metastases had been detected.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, there is a long delay (range, 4 to 228 months; median, 40 months) between the excision of the primary skin lesion and the emergence of metastases. Actually, long-term follow-up shows that those metastases, whatever their location, are characteristically slow-growing lesions, which justifies the iterative metastasectomy approach in case of pulmonary involvement (7,8). This is exemplified by Patient 1 of our series in whom a progressive inguinal lymph node enlargement was noticed as long as 13 years before inguinal lymphadenectomy and also by Patient 2 of Colome-Grimmer and Evans's report (7), who survived 8 years after his lung metastases had been detected.…”
Section: Discussionmentioning
confidence: 99%
“…The neoplastic cells contained enlarged vesicular nuclei, numerous mitoses (up to 50 mitoses in 10 high-power fields), and did not stain positively for CD34, S-100 protein and alpha-smooth muscle actin. The tumor showed multiple chromosomal aberrations including gains of chromosomes 1, 3, 7, 18, 22 and losses of chromosomes 4,5,6,7,8,9,11,12,13,18,19 indicating a marked genomic instability and an aggressive biological behavior (data not shown). Within 1 year the patient developed lung and retroperitoneal metastases and died of the disease.…”
Section: Methodsmentioning
confidence: 97%
“…During the past years a few examples of cellular, aneurysmal, atypical dermatofibromas as well as of dermatofibromas occurring on the face and in deep soft tissues have been reported that metastasized to lymph nodes and the lungs and even caused death of patients in some instances. 1,4,[6][7][8][9][10][11][12][13][14] Morphologically, the primary and the metastatic neoplasms showed classical features of the mentioned variants of dermatofibroma, and so far no predictive mophological features have been identified to separate classical benign dermatofibroma from rare metastasizing dermatofibroma. In this study, we investigated seven cases of malignant dermatofibroma in comparison with 10 examples of classical dermatofibroma and to 1 obvious pleomorphic dermal sarcoma not otherwise specified.…”
mentioning
confidence: 99%
“…DF almost pursues a benign course, with a recurrence rate of less than 2%, although a higher rate of recurrence has been reported for some variants, including the cellular, aneurysmal, and atypical (pseudosarcomatous) forms 14 . A higher rate of recurrence has been noted in the subcutaneous and deep types and in lesions located on the face, in which a recurrence rate of 15% has been reported 6,15 . Also, a local recurrence rate of 19% (four of 21 cases) has been reported in 21 cases from the previous subcutaneous DF series 2 .…”
Section: Discussionmentioning
confidence: 97%